Language Revolt in Paradise: Recent Indonesian Non-Conventional Expressions - Basthomi, Yazid (k@ta: A Biannual Publication on the Study of Language and Literature, 2010)
Language is dynamic and, accordingly, language change is bound to occur. This article analyzes few recent Indonesian non-conventional expressions as properties which potentially motivate some changes in Bahasa Indonesia (Indonesian). Since the term “non-conventional” has to do with the notion of “convention”, which is central to Saussurean linguistics, the analysis is carried out by means of Saussure’s linguistic views. The analysis shows that the non-conventional expressions can be well accounted for using Saussure’s theoretical propositions. However, as to why Indonesians come up with the non-conventional expressions is beyond pure Saussure’s linguistic concepts. The article also touches upon the idea that the issue about non-conventional expressions (which may be deemed grammatical aberrations) poses a challenge to language planners.